Developing biology enrichment book of fish diversity of aquatic ecosystems in Kampar District - Firman Syah; Y. Yustina (University of Muhammadiyah Malang, 2021)
Fish diversity in Kampar District is one of natural resources which is potentially developed as a contextual learning resource for student. This Research and Development (R&D) study aimed at developing biology enrichment book of fish diversity in Kampar District as learning resource for X graders. The R&D model employed was ADDIE which was limited to the third phase (i.e development). The validity and practicality tests on the product developed were conducted by material and media experts as well as 20 biology teachers. The instrument used was questionnaire with five Likert scale. It comprised of 18 items in which the 10 items related to content eligibility and material presentation, meanwhile, the other eight items related to language and graphics. The results showed that the product developed was categorized as very valid with several minor revisions. The overall practicality test resulted the score value with high practicality category (83.8). In addition, the results of development stage depicted that the biology enrichment book of fish diversity in Kampar District was categorized as strongly valid. Thus, it can be continued to the next stage in term of implementation and evaluation in order to get the usable product for student as a contextual learning resource.